Paraconiothyrium sp. P83F4/1: Antioxidant and Antiproliferative Activities an Endophytic Fungus Associated with Rheedia brasiliensis Plant - Dumitriu, Brindusa Georgiana; Olariu, Laura; Ene, Diana Manuela; Zglimbea, Lenus; Rosoiu, Natalia (International Journal of Biotechnology for Wellness Industries, 2012)
The endophyte Paraconiothyrium sp. P83F4/1 was isolated from leaves of the Rheedia brasiliensis medicinal plant from a bioprospecting study. To the best of researcher’s knowledge, this is the first report of isolation of Paraconiothyrium in leaves of R. brasiliensis and the fermentation product obtained with this fungus in ethyl acetate was evaluated for their potential bioactive through antioxidant assay by DPPH (radical 1,1-diphenyl-2-picrylhydrazyl) method and antiproliferative assays in human tumoral cells using the sulphorhodamine B technique for evaluating the cellular growth. According to the antioxidant assay, tested at 90 µg/mL (90 ppm), the fungal extract showed scavenging capacity of 58.92 %, being significant (p<0.05) compared to the standard commercial butyl hydroxy toluene: 39.52 %. In the antiproliferative assay, the extract was selective on human keratinocyte cells (HaCat) with GI50 0.95 µg/mL, whose mean log GI50= - 0.02, according to National Cancer Institute (NCI-USA) criteria, it makes a powerful extract. HaCat Cells are involved directly in diseases such as psoriasis. These results indicate the antioxidant and antiproliferative potentials of the crude extract of fermentation of the endophytic fungus Paraconiothyrium sp. P83F4/1 isolated from the leaves of R. brasiliensis.